Penerapan Akuntansi pada Usaha Mikro Kecil dan Menengah (Studi pada UMKM Kerupuk Kulit Tradisional Kelurahan Seganteng) - Ni Nyoman Yuliati; Sofiati Wardah; Baiq Widuri (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
This study aims to determine the application of accounting for MSMEs and the constraints faced in the making of financial report for “UMKM Kerupuk Kulit Tradisional” in the Seganteng village. The research uses descriptive method in the form of a survey. The data was obtained through the administration of questionnaires to MSMEs in the Seganteng village, and processed using frequency distribution. The results showed that the majority (68%) of its entrepreneurs had not prepared financial reports due to limited understanding and ability of accounting and bookkeeping. The complexity of the accounting process and the majority of MSME actors considered that financial statements were not an important thing to do. While the remaining 32% only make a simple cash flow reports (cash inflow and outflow). On average, however, MSMEs in Seganteng have implemented accounting practices as 86% have prepared a report on sales and purchases, while only 45% have prepared a report on cash flow.